Protease-resistant cell meshworks: an indication of membrane nanotube-based syncytia formation - Staufer, Oskar; Hernandez Bücher, Jochen Estebano; Rustom, Amin (Experimental cell research, 2018)
Cell biology considers most animal tissues as assemblies of “individual” cells that rely on different contact-dependent communication mechanisms, including synapses, gap junctions or - a recent awareness - membrane nano- and microtubes. However, by protease-mediated singularization of dense 2D/ 3D cell cultures and tissue explants, we show here that cell collectives stay connected via a continuous meshwork of F-actin-based membrane tubes, resembling tunneling nanotube (TNT)-based networks observed between dispersed cell cultures. Fusion of respective tubes was accompanied by the ingrowth of microtubules and the invasion of mitochondria and lysosomes. Remarkably, in homology to the plasmodesmata-based plant symplast, we found evidence for expanded, membrane-based syncytia in animal tissues by observing dye transfer among the highly interlinked cells. This approach allows for the first time to visualize and quantify membrane continuity-based connections among densely packed cells and to assess their potential physiological and pathological impact closer to the in vivo situation.